Comparison of different mosquito trapping methods at the Akrotiri Peninsula - Athanasiou, Katerina C. (My University, 2022)
In this two year (2020 and 2021) study the effectiveness of two different trap types (ovitraps and hay infused ovitraps) and BG Sentinel traps was investigated. Traps were placed at points of entry such as the Limassol port and the RAF Airport and adjacent sites. Traps were placed in order to monitor for invasive mosquitoes such as the Asian tiger mosquito Aedes albopictus (not present yet in Cyprus) but also the native species such as Culex pipiens. The presence of Wolbachia spp. in Culex pipiens mosquitoes was also investigated in the laboratory of the Cyprus University of Technology. More mosquitoes were caught in the hay infused ovitraps compared to the ovitraps in the first year while in the second year the opposite was true. Due to technical issues we were not able to identify Wolbachia spp. in mosquitoes during the laboratory study.
Keywords: Mosquito Traps; Culex pipiens; Wolbachia spp.; Wolbachia spp.